2022
DOI: 10.4244/aij-d-22-00022
|View full text |Cite
|
Sign up to set email alerts
|

Coronary physiology in the catheterisation laboratory: an A to Z practical guide

Abstract: Coronary revascularisation, either percutaneous or surgical, aims to improve coronary flow and relieve myocardial ischaemia. The decision-making process in patients with coronary artery disease (CAD) remains largely based on invasive coronary angiography (ICA), even though until recently ICA could not assess the functional significance of coronary artery stenoses. Invasive wire-based approaches for physiological evaluations were developed to properly assess the ischaemic relevance of epicardial CAD. Fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 135 publications
0
7
0
1
Order By: Relevance
“…Similar results were previously reported, suggesting that the agreement between angiography-derived IMR and invasive IMR was very close in NSTEMI and CCS, whereas it was less accurate in the STEMI setting. The inherently higher biological variability of IMR in a STEMI setting could explain such a difference, as the absolute numerical IMR values were less well correlated with the standard of reference in the case of extreme CMD [13,14,35]. This might be related to the hyper-sympathetic activation and the profound structural microvascular deterioration since the early phases (i.e., microvascular clotting, leukocyte adhesion and distal embolization) [13,14,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were previously reported, suggesting that the agreement between angiography-derived IMR and invasive IMR was very close in NSTEMI and CCS, whereas it was less accurate in the STEMI setting. The inherently higher biological variability of IMR in a STEMI setting could explain such a difference, as the absolute numerical IMR values were less well correlated with the standard of reference in the case of extreme CMD [13,14,35]. This might be related to the hyper-sympathetic activation and the profound structural microvascular deterioration since the early phases (i.e., microvascular clotting, leukocyte adhesion and distal embolization) [13,14,35].…”
Section: Discussionmentioning
confidence: 99%
“…The inherently higher biological variability of IMR in a STEMI setting could explain such a difference, as the absolute numerical IMR values were less well correlated with the standard of reference in the case of extreme CMD [13,14,35]. This might be related to the hyper-sympathetic activation and the profound structural microvascular deterioration since the early phases (i.e., microvascular clotting, leukocyte adhesion and distal embolization) [13,14,35]. Thus, in the setting of functional CMD, the use of hyperemic angiograms to compute AMR might be considered, as previously reported for the FFR/QFR disagreement [36].…”
Section: Discussionmentioning
confidence: 99%
“…25 Conversely, inconsistent unpredictable variations of iFR and other nonhyperemic indexes were reported between pre- and post-TAVI. 6,20,26 Based on a substudy of the NOTION-3 (Third Nordic Aortic Valve Intervention) including 50 vessels with FFR and 36 vessels with resting full-cycle ratio measured pre- and 6 months after TAVI, Sabbah et al 5 showed that resting full-cycle ratio improved significantly (0.88–0.92; P =0.003), whereas FFR remained unchanged (0.84–0.86; P =0.72). Moreover, a low rate of lesion reclassification was seen with FFR (FFR-positive 22%–30%; P =0.219) compared with resting full-cycle ratio (resting full-cycle ratio-positive 64%–33%; P =0.003).…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, PW-based physiological assessment is associated with increased procedural costs, radiation, contrast medium exposure, as compared with computational physiological assessment derived from a single angiographic projection. 20 The use of coronary physiology in the management of SAS has the potential for simplifying the clinical management of patients with bystander CAD, by reducing the need for stenting, number of stents used, and for dual antiplatelet therapy. The effectiveness of an FFR-guided revascularization in reducing the number of vessels with significant disease and improving survival without major adverse cardiac events was previously reported in retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these major trials support the class IA recommendation to assess the hemodynamic relevance of intermediate coronary artery disease by FFR and as class IIB in multivessel disease evaluation[ 8 ]. In fact, both the European and American guidelines state that patients undergoing coronary angiography without prior ischemia assessment should have invasive hemodynamic test (FFR or NHPR) to optimize the revascularization strategy[ 40 ].…”
Section: Fractional Flow Reservementioning
confidence: 99%